Musical and Rhythmic Structure in Modern Free Poetry : an Analytical Reading of the poem Safar Ayyub - Najem Abdullah, Assist. .Prof. Dr. Ali (Basra studies journal, 2025)
The research aims at revealing the musical and rhythmic structure in free poetry through an analysis of the poem (safar Ayyub) by the Iraqi poet Badr Shaker Al-Sayyab. The research dealt with how the poet employs the musical and rhythmic structure in the mentioned poem as an applied model and how these elements contribute to enhancing the meanings and symbols presented in the text. Accordingly, an analysis of the method that the poet used to achieve this musical and rhythmic effect is explained. The research included: The introduction, then the first section, which included: the problem of the study, its objectives, importance, limits, and terminology. The second section the theoretical framework included two sections: the first one devoted for explaining musical structure in free poetry, and the second part was about the innovative image in the poetry of Badr Shaker Al-Sayyab. The third section dealt with the analytical framework: Research methodology, research population, research sample, research tools and requirements, validity and reliability of the tool, analysis of the research sample, then the fourth section includes a presentation of the research results, conclusions, and recommendations .